Transient Acquired Hypoventilation Syndrome Secondary to Uncal Herniation Is Successfully Treated with Bilevel Noninvasive Positive Pressure Ventilation. (17th December 2018) - Hou, Linle; Stoll, Jonathan; Pioppo, Lauren; Xu, Jack; Khan, Wajahat
Abstract : Background. To describe an unusual presentation of acquired hypoventilation syndrome treated successfully with noninvasive positive pressure ventilation. Case Presentation. We report a case report of a 48-year-old male who presented to the emergency room for recurrent syncope. He was found to have a ventricular colloid cyst causing uncal herniation. The patient was noted to be intermittently apneic and bradypnic. Transient hypoventilation was successfully treated with noninvasive positive pressure ventilation and the patient made a full neurological recovery following transcallosal resection of the colloid cyst. Subsequently, the hypoventilation resolved. Conclusion. With prompt surgical intervention, full neurological recovery is possible after cerebral uncal herniation. In rare circumstances, this can result in transient alveolar hypoventilation. Bilevel noninvasive positive pressure ventilation can be used to successfully manage the hypoventilation.